2014
DOI: 10.1080/01635581.2014.895392
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment withEpimedium koreanumNakai Extract and Gefitinib Overcomes Drug Resistance Caused by T790M Mutation in Non-Small Cell Lung Cancer Cells

Abstract: Although the epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors, such as gefitinib, have shown promising therapeutic efficacy in nonsmall cell lung cancer (NSCLC) patients harboring EGFR activating mutation, development of acquired resistance is almost inevitable. We investigated whether the addition of Epimedium koreanum Nakai extract (EEF) to gefitinib could overcome the resistance of NSCLC cells to gefitinib. In our study, the growth inhibitory effects of cotreatment differed between mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…NSCLC patients with an Arg substitution for Leu at position 858 or a deletion of exon 19 in EGFR are responsive to EGFR TKIs [ 38 ]. Several clinical studies have indicated that the amplification of a T790M mutation in EGFR contributes to the acquisition of EGFR TKI resistance [ 39 ]. Therefore, TKI-sensitive lung cancer cell lines (PC9, exon 19 deletion; H3255, L858R EGFR mutant) [ 40 ] and TKI-resistant lung cancer cell lines (PC9/gef, exon 19 deletion, acquired resistance; H1975, L858R/T790M EGFR mutant) [ 38 ] were used to evaluate the anticancer effectiveness of digoxin.…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC patients with an Arg substitution for Leu at position 858 or a deletion of exon 19 in EGFR are responsive to EGFR TKIs [ 38 ]. Several clinical studies have indicated that the amplification of a T790M mutation in EGFR contributes to the acquisition of EGFR TKI resistance [ 39 ]. Therefore, TKI-sensitive lung cancer cell lines (PC9, exon 19 deletion; H3255, L858R EGFR mutant) [ 40 ] and TKI-resistant lung cancer cell lines (PC9/gef, exon 19 deletion, acquired resistance; H1975, L858R/T790M EGFR mutant) [ 38 ] were used to evaluate the anticancer effectiveness of digoxin.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro scratch‐wound analysis was performed as previously described . After scratched with a 200 µl pipette tip, the wounded cultures of A549 or H1299 monolayers were rinsed twice with PBS to eliminate non‐adherent cells and further treated for 24 h, as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear protein was isolated using the Nuclear Extraction Kit (Keygen Biotech, Nanjing, China). Antibodies against E‐cadherin, N‐cadherin, vimentin, GSK‐3β, phospho‐GSK‐3β, phospho‐Akt, phospho‐Akt, NF‐κB p65, phosphorylated p65, AP‐1, IκBα, phosphorylated IκBα, Lamin A (Santa Cruz, CA), Slug, Snail, phospho‐ERK1/2, ERK1/2, β‐actin (Cell Signaling Technology, Danvers, MA) were used to detect protein levels by Western blot analysis, as described previously . The signal was detected using an enhanced chemiluminescence kit (Boster, Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%
“…A549 cells were cultured in high-glucose DMEM, supplemented with 10% FBS, at 37°C in a 5% CO 2 atmosphere. 16 The medium was changed every other day. When the cells reached 90% confluence, they were trypsinized with 0.25% trypsin-EDTA and subcultured.…”
Section: Dl%mentioning
confidence: 99%